2020
DOI: 10.1111/1475-679x.12334
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Tax Enforcement Externalities and the Banking Sector

Abstract: We explore whether corporate tax enforcement can affect bank lending. Specifically, we hypothesize that tax enforcement efforts aimed at small and midsized enterprises (SME) can improve their information environments, which in turn could lead to increased bank commercial lending. Exploiting the regional structure employed by the IRS until 1999, we find that the corporate tax return audit probability for SMEs is associated with greater commercial lending growth for regionally focused banks. We find similar evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Guedhami and Pittman found that tax administration and enforcement can induce firms to improve the quality of accounting information, increase information transparency, and reduce information asymmetry, thereby alleviating corporate financing constraints [10]. Gallemore and Jacob also argued that tax administration could improve the information environment of banks and SMEs, enabling banks to make more rational lending decisions and thus increase the probability of receiving credit support for SMEs [29]. Ye et al found that tax administration via big data can significantly improve the robustness of corporate accounting by increasing the transparency of corporate information, and this effect is more pronounced in firms with weaker external monitoring and tax collection [17].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Guedhami and Pittman found that tax administration and enforcement can induce firms to improve the quality of accounting information, increase information transparency, and reduce information asymmetry, thereby alleviating corporate financing constraints [10]. Gallemore and Jacob also argued that tax administration could improve the information environment of banks and SMEs, enabling banks to make more rational lending decisions and thus increase the probability of receiving credit support for SMEs [29]. Ye et al found that tax administration via big data can significantly improve the robustness of corporate accounting by increasing the transparency of corporate information, and this effect is more pronounced in firms with weaker external monitoring and tax collection [17].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Recent research shows that besides causing costs, tax audits may also have positive effects for firms. Specifically,Guedhami and Pittman (2008) show that a higher audit probability reduces the costs of debt financing, andGallemore and Jacob (2020) show that a higher audit probability increases commercial bank lending to firms. In general, however, it can be assumed that the costs of audits exceed potential benefits.4 Firms worldwide spend approximately 25 hours complying with the requirements of an auditor and spend almost 11 weeks going through several rounds of interactions with the auditor according to The World Bank (2017).…”
mentioning
confidence: 99%